The differences in tendency of aggressive behaviour, emotional intelligence and antisocial personality between gender and between family system among undergraduate university students Lahore, Pakistan - Rabi, Imdad; Redzuan, Ma'rof; Abdullah, Haslinda; Hamsan, Hanina Halimatusaadiah (Human Resource Management Academic Research Society, 2018)
In the study independent Samples t-test was used to identifying difference in tendency of aggressive behavior, antisocial personality and emotional intelligence between gender and family system groups. The finding indicated that no significant difference in antisocial personality, emotional intelligence and tendency of aggressive behavior between genders. The findings indicated that students from nuclear families showed a higher tendency of aggressive behavior than those from joint families. Similarly students from nuclear families showed higher antisocial personality than those from joint families. In addition students from joint families were found to have higher emotional intelligence than students from nuclear families.